Dipeptidyl peptidase‐4 inhibitors as preferable oral hypoglycemic agents in terms of treatment satisfaction: Results from a multicenter, 12‐week, open label, randomized controlled study in Japan (PREFERENCE 4 study). Issue 1 (2nd May 2017) - Ishii, Hitoshi; Hayashino, Yasuaki; Akai, Yasuhiro; Yabuta, Matahiro; Tsujii, Satoru
Abstract : To compare the treatment satisfaction of four classes of oral hypoglycemic agents (OHAs): dipeptidyl peptidase‐4 (DPP‐4) inhibitors, α‐glucosidase inhibitors (aGI), biguanides (BG), and sulfonylureas (SU), and to identify the best OHA in terms of treatment satisfaction, a 12‐week, randomized, controlled, open‐label study was conducted among Japanese outpatients with type 2 diabetes mellitus using the Oral Hypoglycemic Agent Questionnaire. In conclusion, the DPP‐4 inhibitor was the most preferable option in terms of treatment satisfaction. Abstract: Aims/Introduction: To compare the treatment satisfaction of four classes of oral hypoglycemic agents (OHAs): dipeptidyl peptidase‐4 (DPP‐4) inhibitors, α‐glucosidase inhibitors (αGI), biguanides (BG) and sulfonylureas (SU), which are common initial treatments for type 2 diabetes mellitus patients in Japan, and to identify the best oral hypoglycemic agent in terms of treatment satisfaction. Materials and Methods: In this 12‐week, randomized, controlled, open‐label study, Japanese outpatients with type 2 diabetes mellitus who were naïve to pharmacological treatment were randomly assigned a DPP‐4 inhibitor, a BG., an αGI or a SU. The primary end‐point was the Oral Hypoglycemic Agent Questionnaire (OHA‐Q) total and subscale scores (treatment convenience, somatic symptoms and satisfaction) at week 4. Adherence, glycated hemoglobin (HbA1c) level and safety were also evaluated. Results: The DPP‐4 inhibitor group scored highest in the OHA‐Q total and all subscale scores at week 4. The total score was significantly higher in the DPP‐4 inhibitor group than in the BG or αGI groups ( P = 0.0084 and 0.0147, respectively). The mean total score at week 12 was also highest in the DPP‐4 inhibitor group, with a significant difference compared with the αGI group ( P = 0.0293). The mean HbA1c decreased from baseline to week 12 in all groups. The DPP‐4 inhibitor group had the highest adherence at weeks 4 and 12. A total of 11 patients reported adverse events, including one hypoglycemic event in the SU group. Conclusions: The DPP‐4 inhibitor was the most preferable option in terms of treatment satisfaction.